Shish-kebab - Lampila, Seija, 1936-2021; PSO (levy-yhtiö) ([Helsinki] : [PSO], 1958)
4 kappaletta.
Ilmestyneet myös singleinä: A -puoli BLU542 ; B -puoli BLU544.
Seija Lampila (lauluääni).
Äänitys: 1958.
[Äänite]